1992
DOI: 10.1002/jcp.1041530216
|View full text |Cite
|
Sign up to set email alerts
|

Growth factors produced by human embryonic kidney cells that influence megakaryopoiesis include erythropoietin, interleukin 6, and transforming growth factor‐beta

Abstract: Partially purified protein preparations containing megakaryocyte growth factor activity were prepared from human embryonic kidney (HEK) cell conditioned medium using ammonium sulfate precipitation, Cibicron blue affinity chromatography, and wheatgerm lectin affinity chromatography. Treatment of these preparations with neutralizing antibodies directed against erythropoietin (EPO) and interleukin 6 (IL6) resulted in a dramatic reduction in their capacity to stimulate megakaryocyte maturation in vitro. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
(41 reference statements)
2
9
0
Order By: Relevance
“…In the present study, we observed that infusion of HEK cells or HEK-CM enhanced the endogenous mRNA level of EPO in the host brain. A previous study demonstrating the presence of EPO in HEK-CM and its role in megakaryopoiesis supports our findings [11]. EPO exerts its neuroprotective action by activating intracellular cell survival pathways such as the PI3K/Akt pathway that ultimately activates the anti-apoptotic factors, including Bcl-2 [15].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, we observed that infusion of HEK cells or HEK-CM enhanced the endogenous mRNA level of EPO in the host brain. A previous study demonstrating the presence of EPO in HEK-CM and its role in megakaryopoiesis supports our findings [11]. EPO exerts its neuroprotective action by activating intracellular cell survival pathways such as the PI3K/Akt pathway that ultimately activates the anti-apoptotic factors, including Bcl-2 [15].…”
Section: Discussionsupporting
confidence: 91%
“…Nonetheless, the recent consensus is that the host tissue regeneration may be partly attributed to the paracrine effects of transplanted cells, which in turn activate the host's endogenous reparative mechanisms for cellular and functional recovery [8e10]. In this context, conditioned media (CM) derived from cell cultures are excellent sources of neurotrophic factors and cytokines [11,12]. Though the majority of studies investigated the effects of cell transplantation in animal models of hippocampal neurodegeneration [6,7], there is not much information available on the effects of CM per se in cellular and behavioral recovery after hippocampal damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that megakaryocytes do indeed respond to growth factors or contain receptors for them. 15,34 In practice, this scenario (misinterpreting nMEG pSTAT5 immunoreactivity because of growth factors for a JAK2 V617F+ CMPD) is unlikely to represent a diagnostic problem, because suspected CMPD patients are not usually treated with growth factor therapies. Furthermore, a careful clinical history would easily resolve the matter.…”
Section: Discussionmentioning
confidence: 99%
“…43 Unlike IL-5, which is eosinophil-specific, IL-6 influences the proliferation of multipotent myeloid progenitor cells, and also stimulates human megakaryocyte maturation and differentiation in vitro. 44,45 EPO and TPO are two lineage-specific hematopoietic growth factors that are produced primarily by the kidney 46 and liver, 47 respectively. EPO regulates erythrocyte production while TPO functions to regulate platelet production.…”
Section: Mpl Pluripotent Stem Cells Megakaryocytes and Their Progenitorsmentioning
confidence: 99%